Election Campaigning During Pandemic: A Rhetorical Study of President Nana Addo Dankwa Akufo Addo's Corona Virus Update Speeches - Dotsey, Jennifer Akpene (UniMAC-GIJ, 2021)
The study assesses whether or not President Nana Akufo-Addo used campaign rhetoric in his Corona virus update speeches. Employing a qualitative research design, the study purposively sampled and analysed nineteen (19) corona virus update speeches from March 12 2020, to November 8, 2020. The findings revealed that President's corona virus update speeches have four major components: issues, homestyle, image, and persuasion (emotional appeal) strategies. The COVID-19 update allows the ruling government to run a campaign on the platform. Also, the findings showed that the corona virus update speeches were written to appeal to Ghanaians' emotions to convince them to vote for President Nana Akufo-Addo. Also, the President’s corona virus update speeches extensively used campaign rhetoric image strategies, projecting the leadership exhibited in the management of the COVID-19 pandemic. It is recommended that there is the need to reconsider such approaches in writing speeches for the President. This is because the rhetorical strategy commonly employed by incumbents may be less powerful in terms of rival party defections. Also, too much focus on issues/image strategy should be avoided in campaign speeches.
Thesis
Keywords: Election Campaigning, Pandemic, President Nana Addo Dankwa Akufo Addo, Corona Virus, Ghana